2022
DOI: 10.1111/jhn.13111
|View full text |Cite
|
Sign up to set email alerts
|

Sources of nutrition advice and desired nutrition guidance in oncology care: Patient's perspectives

Abstract: Background: The present study aimed to describe the proportion of cancer patients and survivors who receive nutrition advice, the sources of that advice and to explore the nutrition advice this cohort would like to have received. Methods: A descriptive cross-sectional survey was completed by 211 cancer patients and survivors recruited through two hospitals in the North-West of Ireland. The survey consisted of open-ended and closed questions that aimed to explore the provision of and sources of nutrition advice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
(78 reference statements)
0
2
0
Order By: Relevance
“…However, dietary changes are often small and not necessarily clinically relevant, suggesting a need for expert nutritional support [ 18 ]. In high-income countries it is estimated that between 30 to 50% of people with cancer and cancer survivors receive dietetic care, a service that is strongly desired by this group of individuals [ 19 , 20 ]. Previous research has demonstrated that dietitians who provide care to people with head and neck cancer demonstrate high rates of awareness and implementation of evidence-based nutrition guidelines [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, dietary changes are often small and not necessarily clinically relevant, suggesting a need for expert nutritional support [ 18 ]. In high-income countries it is estimated that between 30 to 50% of people with cancer and cancer survivors receive dietetic care, a service that is strongly desired by this group of individuals [ 19 , 20 ]. Previous research has demonstrated that dietitians who provide care to people with head and neck cancer demonstrate high rates of awareness and implementation of evidence-based nutrition guidelines [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…7 This ranges from information that is not easily translated into practice to the downright misleading, which is not a surprise in the era of the internet, but a huge cause for concern. The breadth of topics that people wish to access range from the desire for dietary advice to the frustration around lack of clarity of nutrition guidance is well described by Keaver et al 8 Dietitians were identified as the professional of choice to be the primary source of this nutrition advice, which is a feeling strongly echoed by the dietetic profession. The complex nature of cancer, as well as the nutrition and supportive care needs of people with a particular cancer diagnosis, is highlighted in the work of Hiatt et al 9 Head and neck cancer presents specific challenges with respect to nutrition and the additional support people need during and after treatment.…”
mentioning
confidence: 99%